Pengaruh Ketidakpastian Lingkungan Dan Karakteristik Informasi Akuntansi Manajemen Terhadap Kinerja Manajerial (Studi Pada Perusahaan Bumn Di Jawa Timur) - Reni Dwi Jayanti, ; Heri Widodo, (Bisnis dan Manajemen, 2010)
The objective of the study is to identify the relationship between uncertainty environment variable and characteristic variable of management accounting information toward the managerial work performance variable at BUMN organization in East Java. The sample is taken from the population of managers and their assistants in the organization. The study uses simple random sampling technique. The result of the study proves that the uncertainty environment variable and management accounting information influence the managerial work performance variable simultaneously. Temporarily, the characteristics variable of management accounting information influences the managerial work performance partially. The study determination coefficient is 16.7%, and its remnants (83.3%) shows that the managerial work performance variable influenced by the other variables out of the study.